Chronic kidney disease of unknown etiology in agricultural communities - Tungsanga, Somkanya; Katavetin, Pisut (Journal of the Nephrology Society of Thailand, 2022)
The prevalence of chronic kidney disease in specific areas, including Nicaragua, El Salvador, Sri Lanka and India, has upsurged during the past decades. This emerged unrelated to traditional risk factors, such as diabetes, hypertension or glomerulonephritis, so called ‘chronic kidney disease of unknown etiology (CKDu)’, and could lead to morbidity and mortality. The prevalence was reported highest among young male sugarcane workers in endemic areas. The etiology of the disease remains unknown. However, agrochemical use, heat stress, dehydration, water contamination, leptospirosis, herbal medicines, and genetic susceptibility were found to be the associated factors. Because patients with CKDu were mostly asymptomatic, they presented in advanced stages. The primary pathological findings consisted of tubulointerstitial fibrosis. No specific treatment was provided beyond standard CKD care. Proving the definite cause of the disease would lead to effective disease prevention and attenuation of disease progression. We herein discuss the epidemiology, endemic nephropathies, clinical manifestations in acute and chronic phases, pathologic findings, possible etiology, treatment, and prevention strategies of CKDu.